Gender inequalities in labour market outcomes: Evidence for Greek regions before and throughout the crisis. Issue 5 (7th August 2017) - Georgiadis, Thomas; Christopoulos, George
Abstract : Purpose: The purpose of this paper is to focus on the investigation of gender inequalities in the labour market at the regional level in Greece throughout the years preceding and following the economic crisis. Design/methodology/approach: Utilising microdata from the European Union Statistics on Income and Living Conditions (EU-SILC) database from 2005 up to the most recent available, the authors construct the Total Earnings Gap Index, a composite index at the individual level which incorporates gender differentials in aspects related to employment, work intensity and earnings. This approach is further complemented by the results of the econometric analysis (a probit model for the probability of being in employment and a Heckman selection model for the determinants of hourly pay and hours worked), which portray the impact of gender on a set of labour-related characteristics. Findings: The findings of the analysis indicate a widespread reduction of the gender gap; however, this appears to be mainly the result of a sharper fall in employment among men, hence pointing towards a "race to the bottom" process which presents few – if any – signs of an increase of women's economic independence. The emerging picture points towards a trend of regional convergence in gender gaps, while also highlighting that similar gender equality outcomes are, in certain cases, shaped by radically different dynamics. Originality/value: This paper uses an innovative composite index which provides a multi-dimensional depiction of gender inequality in the Greek labour market. This index has been introduced by Eurostat and has been applied at the country level, with this paper being the first – to the authors' knowledge – to apply it at the regional level. Additionally, by examining years before and throughout the crisis, the present analysis adopts a dynamic perspective, offering valuable insight into the seismic shifts that Greece's labour market structure has undergone during this period.